Parental Satisfaction Assessment After Paediatric Procedural Sedation: There Are Still Issues to Address - (:unkn) unknown (My University, 2014)
OBJECTIVE: As paediatric sedation practices are becoming safer and more feasible everyday, they have been widely used for diagnostic and therapeutic procedures. This study intended to determine the relation between parental satisfaction and the branches applying procedures and demographic data of the patients and their families, physicians, nurses, and the healthcare personnel in the room. METHODS: In total, 223 successive patients under 18 years of age and ASA I-II undergoing diagnostic or therapeutic procedures in paediatric pulmonary disease, gastroenterology, cardiology, and invasive radiology units were included in the study. The satisfaction level of the patients' parents was determined through a questionnaire of 22 questions. RESULTS: Average satisfaction scores for paediatric bronchoscopy and endoscopic interventions varied between 8.06 and 9.30, while the satisfaction scores of the interventions for the cardiovascular system, hepatic system, and renal system, as well as the invasive radiologic interventions, varied between 7.5 and 9.6. There was a statistically significant negative correlation between the age of parents and children and the necessity for a playground in the waiting area (p<0.05). A significant correlation was found between the age of children and the adequacy of the anaesthetist's behaviors (p<0.05). CONCLUSION: Satisfaction levels of the parents were high at the units where paediatric sedation was applied. However, the expectations of young patients and their parents were higher. When the physical conditions and communication with patients and their relatives are improved and the process schedules are followed more precisely, the clinical results will increase in a positive way.
Keywords: questionnaire; children; paediatric; Parental satisfaction; sedation